THE ROLE OF ISLAMIC FINANCIAL INSTITUTIONS IN EMPOWERMENT SME’S IN INDONESIA - Maulana, Irwan (Islamic Banking & Economic Law Studies (I-BEST), 2022)
Syariah Financial Institution means that the financial institution is run based on the Islamic teaching that refers to Qur’an and the Sunnah. Practically, it began in early history of islam, then was developed into Syariah Financial Institution. So, the purpose of Syariah Financial Institution is not merely for profit orientation. Further, it should be in accordance with Islamic value and the human philantrophy. Most of Syariah Financial Institution’s financing is for busines sector and its ability to reach the micro business, that can’t be done by commercial banks. The financing for small business is funded by islamic institutions due to Grameen Bank effect. Previously, Grameen Bank was built in mid-decade of 1970. The Financing of Syariah Financial Institution, in any sort, including cooperative union or BMT (Baitul Maal wa Tamwil), increased overtimein both Institution Revenue and the Financing Rate. According to Financial Service Authority, most of financing of Syariah Banking is for the Micro, Small, Medium Enterprises that is very important for the nation economy, because it is engaged in the real sector of economy.